Optical calibration of the SNO+ detector in the water phase with deployed sources. (19th October 2021) - Anderson, M.R.; Andringa, S.; Askins, M.; Auty, D.J.; Barão, F.; Barros, N.; Bayes, R.; Beier, E.W.; Bialek, A.; Biller, S.D.; Blucher, E.; Boulay, M.; et al.
Abstract: SNO+ is a large-scale liquid scintillator experiment with the primary goal of searching for neutrinoless double beta decay, and is located approximately 2 km underground in SNOLAB, Sudbury, Canada. The detector acquired data for two years as a pure water Cherenkov detector, starting in May 2017. During this period, the optical properties of the detector were measured in situ using a deployed light diffusing sphere, with the goal of improving the detector model and the energy response systematic uncertainties. The measured parameters included the water attenuation coefficients, effective attenuation coefficients for the acrylic vessel, and the angular response of the photomultiplier tubes and their surrounding light concentrators, all across different wavelengths. The calibrated detector model was validated using a deployed tagged gamma source, which showed a 0.6% variation in energy scale across the primary target volume.